Quorum quenching revisited-from signal decays to signalling confusion - Hong, Kar Wai; Koh, Chong Lek; Sam, Choon Kook; Yin, Wai Fong; Chan, Kok Gan (2012)
In a polymicrobial community, while some bacteria are communicating with neighboring cells (quorum sensing), others are interrupting the communication (quorum quenching), thus creating a constant arms race between intercellular communication. In the past decade, numerous quorum quenching enzymes have been found and initially thought to inactivate the signalling molecules. Though this is widely accepted, the actual roles of these quorum quenching enzymes are now being uncovered. Recent evidence extends the role of quorum quenching to detoxification or metabolism of signalling molecules as food and energy source; this includes "signalling confusion", a term coined in this paper to refer to the phenomenon of non-destructive modification of signalling molecules. While quorum quenching has been explored as a novel anti-infective therapy targeting, quorum sensing evidence begins to show the development of resistance against quorum quenching.